Production and electrophoresis-based purification of recombinant green fluorescent protein from Escherichia coli - Chew, Few Ne (2011)
Green fluorescent protein (GFP) can be used as markers in numerous bioscience applications due to its visible fluorescence. Availability of a reliable and affordable GFP quantitation device is important for these applications. GFP can be quantitated with a spectrofluorometer, but the accuracy of spectrofluorometric method is affected by the present of biomass and it cannot be used to differentiate the nativity of a GFP. Therefore, one of the objectives of this study was to develop a GFP quantitation method using gel-based imaging analysis. The precision, detection limit, linearity, reproducibility and accuracy of this quantitation method were investigated to demonstrate its reliability and suitability for practical application. Besides, the sensitivity and GFP nativity differentiation test were performed and compared with those obtained with a spectrofluorometer. The cultivation conditions for the GFP production in Escherichia coli BL21(DE3) were optimized using statistical experimental designs. The process variables include agitation rate, temperature, pH of medium, inducer concentration, induction time and inoculum density were screened using the fractional factorial design. The screening step identified that agitation rate, temperature and cell density for protein expression have significant effects on GFP production. Hence, these process variables were further optimized using the Box-Behnken design. The optimal cultivation conditions were 206 rpm agitation rate at 31°C and cell density (OD600 nm) of 1.04 for protein expression. The predicted GFP yield (0.234 g/L) is corresponded well with that obtained experimentally (0.241 g/L). The GFP yield achieved under the optimized conditions is 9-folds higher than that of the unoptimized conditions (0.025 g/L). A similar protein yield was achieved when these optimized conditions were applied in a 2-liter stirred tank bioreactor fermentation. Cell disruption is an important step in intracellular protein purification. However, this additional step resulted in a substantial protein loss and increased the overall processing time. Hence, a direct purification method of recombinant GFP from intact E. coli cells was developed using a preparative native polyacrylamide gel electrophoresis. This direct purification process has eliminated the cell disruption step. The cellular content of E. coli was drifted out from cells by the electrophoretic force. The GFP was further separated from other intracellular proteins through a gel and recovered by electrophoretic elution. The effects of the operating parameters including the feedstock volume, feedstock concentration, concentration of resolving gel and height of resolving gel on the purity and yield of GFP were further investigated. At 100 µL feedstock volume, 15% (w/v) feedstock concentration, 12% (w/v) resolving gel concentration and 2 cm resolving gel height, the purity and yield of GFP achieved were 98 and 88%, respectively. The scale-up study has demonstrated that the ratio of feedstock volume to column cross-sectional area at optimal ratio of 44 µL/cm2 was an important factor for scaling-up the purification process. The present study focused on gel electrophoresis technique, which provides the efficient ways to measure the amount of GFP and to purify the intracellular GFP. Besides, an optimal GFP cultivation condition was identified by using statistical experimental designs for maximum GFP production.